Democracy off balance : freedom of expression and hate propaganda law in Canada - Braun, Stefan, 1954- (University of Toronto Press, 2004)
"Freedom of public expression is becoming ever more contested in Canada. The idea that official messages, meanings, and histories can take the place of publicly constructed ones - for fear of what an uncensored public might themselves construct - is gaining widespread acceptance. Public invocation of hate propaganda law, its language, and its moral authority in otherwise ordinary discursive contexts, has contributed to, and is symbolic of, this trend." "Democracy Off Balance offers an analysis of hate censorship as a paradox of modern democratic discourse. In this controversial work, Stefan Braun argues against the supposed public interest served by hate speech laws and dissects the complex forces - the politically self-contradictory thinking and the socially self-defeating assumptions - that drive censorship in Canada today." "Braun draws on censors' own terms of social and political reference to show how they undermine their own causes with hate censorship. He demonstrates how hate speech law reaches beyond its strictly legal confines and essentially conditions and corrodes public discourse. Timely and absorbing, Democracy Off Balance offers a multidimensional approach to the debate and challenges traditional views on the legal boundaries of freedom of expression."--Jacket